National images, trust and international friendship: Evidence from Chinese students. (March 2021) - Davies, Graeme AM; Edney, Kingsley; Wang, Bo
This article uses a new dataset of Chinese student attitudes to foreign affairs to analyse how perceptions of the United States, Russia, Japan and North and South Korea affect respondent perceptions of international friendship with these states. Employing a mediation analysis we find that perceptions of national trustworthiness above all other images is the crucial factor in explaining cross-national friendship. These findings suggest that trust-building measures would be a fruitful avenue for both reducing the likelihood of conflict in the region and fostering cooperative international interactions.